Egy keresztény írás- és olvasásterápia lehetőségei. Szemelvények egy megbékélés-gyakorlathoz - MIKOLA (NYIRI), Emese (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
Opportunities of a Christian Reading and Writing Therapy. Guidelines for an Exercise of Reconciliation. The Second Vatican Council approved the use of scientific results in the Church. According to this, the application of writing and reading therapy for individual or group counselling, supplemented with pastoral purpose is possible. In my point of view, the connection of Christianity to the tradition of texts such as lectio divina, spiritual practice, soliloquia, share many common elements with the techniques of writing and reading therapy. We could use and facilitate the pastoral way of finding God in an enriching and reinforcing way. If we can accompany today’s people, or even ourselves, along the path that Christians have followed for thousands of years and continue to follow, then beyond the benefits of therapy, we can make part from a spiritual community. From this point of view, not only has pastoral psychology been enriched by an old-new counselling method, but also, theology, by a particular path of adult catechesis. In the practical part of my study, I selected seven short texts from the Confessions of St. Augustine of Hippo for the individual practice of reconciliation.